Enhancement Analysis of Damaged Masonry Structures Strengthened with Ultra-High-Performance Concrete - Rui Wang; Wei Wang; Yuecong Zhang; Quan Wen; Xiangguo Wu; Ya Lu; Daiyu Wang; Faqiang Qiu (Buildings, 2025)
In order to enhance the seismic performance of existing masonry structures and optimize the thickness of the strengthening layer, ultra-high-performance concrete (UHPC) can be used as an enhancement material. Based on current concrete strengthening methods, the bearing capacity and seismic behavior of existing masonry structures strengthened with UHPC were investigated numerically. The effects of the strengthening layer thickness and reinforcement ratio on the structural strengthening results were analyzed numerically. The structural behaviors before and after an earthquake, with various strengthening methods, were compared and discussed. The results show that the ratio of axial resistance to shear resistance increases linearly with the resistance ratio. The seismic performance of damaged masonry walls can be improved by about 150% and 250% when 20 mm thick double-sided plain UHPC layers and 30 mm thick double-sided plain UHPC layers are used for strengthening, respectively. The axial compression ratio of masonry walls can be reduced by about 60–70% when double-sided plain UHPC layers are used for strengthening.